2022
DOI: 10.1371/journal.pone.0279613
|View full text |Cite
|
Sign up to set email alerts
|

Factors that affect the utilisation of maternal healthcare in the Mchinji District of Malawi

Abstract: Background It is widely accepted that maternal healthcare is vital for improving maternal and neonatal mortality rates. Furthermore, the continuum of care–the integrated delivery of antenatal, delivery and postnatal care–has been shown to be particularly important. Sub-Saharan Africa has the highest neonatal and maternal mortality rates in the world; significant improvements in the provision and utilisation of the continuum are urgently needed, therefore the barriers preventing access need to be better underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Therefore, the utilization of care continuity needs to be strengthened. A long distance to a health facility [ 50 ], the mother’s low education level [ 23 , 28 , 30 , 31 ], the partner’s low education level [ 48 ], less participation of women in decision-making [ 48 ], economic restrictions [ 24 , 26 29 ], and a lack of knowledge regarding ANC [ 51 ] prevent mothers from utilizing ANC. A delay in a first ANC visit also contributes to less frequency of ANC visits [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the utilization of care continuity needs to be strengthened. A long distance to a health facility [ 50 ], the mother’s low education level [ 23 , 28 , 30 , 31 ], the partner’s low education level [ 48 ], less participation of women in decision-making [ 48 ], economic restrictions [ 24 , 26 29 ], and a lack of knowledge regarding ANC [ 51 ] prevent mothers from utilizing ANC. A delay in a first ANC visit also contributes to less frequency of ANC visits [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this low percentage in our study suggested that health care providers did not sufficiently educate mothers on the importance of delivery with an SBA during ANC. There are also other reasons why women avoid delivery with an SBA or institutional delivery, such as economic restrictions [ 24 , 26 29 ] and a long distance to a health facility [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A unique finding in our study was the lack of guidance and proper follow-up and management of orphaned babies and a mother without a living baby; there is a need to provide guidance and training on how to manage these subgroups so that their care is not compromised. There is limited literature on this aspect however a previous study conducted in Malawi on the overall utilization of maternity services showed that women who had a miscarriage were less likely to use health services [ 29 ]. This area requires more research so that the experiences of such women and babies are unearthed for optimal and inclusive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The ensuing factors have been pointed out as contributors to an increase in the utilization of ANC and SBD services: encouraging females/girls' education [71,113], peer influence, spousal involvement/support in MHC partner education [58,71], partner educator [113,172], education monitoring strategies, unpleasant pregnancy history, employment, media, religion, and pregnancy preparedness. In Uganda, Guinea, Malawi and Ethiopia, studies in these aforementioned countries by Atuhaire et al, Atuoye et al, Stewart et al, and Tareke et al discovered that having decision-making power to visit a health facility, financial independence and easy access to the health facilities were directly linked with ANC and SBD utilization services [56,119,164,180]. • Staffing of medical personnel: nurses, midwives and doctors in a health facility.…”
Section: Determinant Of Anc and Sbd Servicesmentioning
confidence: 99%